Reassignment of vertebrate ichnotaxa from the Upper Carboniferous ‘Fern Ledges’, Lancaster Formation, Saint John, New Brunswick, Canada - Stimson, Matthew; Miller, Randall; Lucas, Spencer (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2016)
ABSTRACT Vertebrate ichnotaxa described by George Frederic Matthew in 1910 from the Upper Carboniferous (Lower Pennsylvanian) ‘Fern Ledges’ of Saint John, New Brunswick, were dismissed as dubious trackways by previous authors. Thus, three new ichnospecies Matthew described appeared in the 1975 Treatise on Invertebrate Paleontology as “unrecognized or unrecognizable” and were mostly forgotten by vertebrate ichnologists. These traces include Hylopus (?) variabilis, Nanopus (?) vetustus and Bipezia bilobata. One ichnospecies, Hylopus (?) variabilis, here is retained as a valid tetrapod footprint ichnotaxon and reassigned to the ichnogenus Limnopus as a new combination, together with other poorly preserved specimens Matthew labeled, but never described. Nanopus (?) vetustus and Bipezia bilobata named by Matthew in the same paper, have been reexamined and remain as nomina dubia.